2022
DOI: 10.1108/bepam-07-2021-0098
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of underground and elevated metro projects from clients' and contractors' perspective

Abstract: PurposeIndia is a rapidly urbanizing developing country with a population of 1.4 Billion. Indian governments have invested USD 50 Billion) in metro rail projects in 18 cities. Metro constructions are multi-stakeholder mega-projects and are prone to a variety of risks. The purpose of this paper is to analyze the risks involved in metro rail construction projects in a densely populated developing country for two types of systems and from two perspectives. Current literature lacks an understanding of similarities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Recently, identification of risk in metro rail projects in India was also undertaken by Patil et al . (2019) and Karmarkar et al . (2022).…”
Section: Time and Cost Causation Risk Factorsmentioning
confidence: 96%
See 4 more Smart Citations
“…Recently, identification of risk in metro rail projects in India was also undertaken by Patil et al . (2019) and Karmarkar et al . (2022).…”
Section: Time and Cost Causation Risk Factorsmentioning
confidence: 96%
“…Historical building preservation problems, relocation risk of people surrounding the project, traffic diversion problems, insurance for all projects and surrounding areas, and political pressure were asserted to be the top five risk factors. In another study in the same context in India on the Risks that trigger cost overruns and delays risk assessment of underground and elevated metro projects, Karmarkar et al (2022) also identified 25 risk factors. The study showed that delay in project approvals and the economic crisis were the two most critical risks from the perspectives of both clients and contractors among the two types of metro systems, elevated and underground.…”
Section: Factors Leading To Cost Overrunmentioning
confidence: 98%
See 3 more Smart Citations